Modulation of chloride homeostasis by inflammatory mediators in dorsal root ganglion neurons - Lehmeyer-Funk, Katharina; Woitecki, Anne; Franjic-Würtz, Christina; Möhrlen, Frank; Frings, Stephan (Molecular pain, 2008)
Background:Chloride currents in peripheral nociceptive neurons have been implicated in the generation of afferent nociceptive signals, as Cl− accumulation in sensory endings establishes the driving force for depolarizing, and even excitatory, Cl− currents. The intracellular Cl− concentration can, however, vary considerably between individual DRG neurons. This raises the question, whether the contribution of Cl− currents to signal generation differs between individual afferent neurons, and whether the specific Cl− levels in these neurons are subject to modulation. Based on the hypothesis that modulation of the peripheral Cl− homeostasis is involved in the generation of inflammatory hyperalgesia, we examined the effects of inflammatory mediators on intracellular Cl− concentrations and on the expression levels of Cl− transporters in rat DRG neurons.Results:We developed an in vitro assay for testing how inflammatory mediators influence Cl− concentration and the expression of Cl− transporters. Intact DRGs were...